TEACHER PRODUCTION AND UTILIZATION FOR EFFECTIVE TECHNICAL EDUCATION DELIVERY IN NIGERIA - Ogunsola, A. L. (Sokoto Educational Review, 2020)
This study examined teacher production and utilization for effective technical education delivery in Nigerian schools. The ex post facto research design was adopted. Four research questions were raised and answered. All the Nigerian tertiary institutions with technical and vocational education programmes between 2001 and 2005 fanned the study population. Fourteen tertiary institutions offering technical and vocational education courses in Nigeria with six technical colleges and sixty teachers in Kogi and Kwara States were selected through simple and stratified random sampling techniques as the study sample. Data which ware collected with checklists and questionnaires were analyzed using percentage, average and bar charts. The study revealed that there was a steady increase in technical-vocational students’ enrolment; that the Colleges of Education produced more vocational teachers than the Universities and Polytechnics; and that graduate teachers with teaching qualification were under-utilized compared with their HND/PGDE and NCE (technical) counterparts. Based on the findings, some workable suggestions are made.